Definition of a Good Death, Attitudes Toward Death, and Feelings of Interconnectedness Among People Taking Care of Terminally ill Patients With Cancer: An Exploratory Study. (May 2020) - Bovero, Andrea; Gottardo, Francesco; Botto, Rossana; Tosi, Chiara; Selvatico, Marta; Torta, Riccardo
The concept of a good death is crucial in palliative care, but its relationship with attitudes toward death and feelings of interconnectedness needs to be further deepened. The first aim of this study was to explore the concept of good death, attitudes toward death, and feelings of interconnectedness among family caregivers (FCs) and health-care providers (HCPs) of terminally ill patients with cancer. The second aim was to analyze associations of good death concept with attitudes toward death and feelings of interconnectedness. Participants were asked to assess the importance of features that characterize a good death. To explore each person's attitude toward death and feelings of interconnectedness, 3 open questions were used. The sample consisted of 49 participants: 24 (48.98%) FCs and 25 (51.02%) HCPs. Nine good death features were considered essential by more than 70% of participants. These referred to the physical (eg, symptoms control), social (eg, loved ones' presence), emotional (eg, sharing emotions), and spiritual (eg, inner peace) dimensions. Importance attributed to components of a good death such as patient's awareness and acceptance of death, meaning, respect for the patient's wishes, and inner peace were found to be associated with lack of avoidance and acceptance toward death and feelings of interconnectedness. Given the importance of FCs and HCPs in providing care and their impact on the patients' dying process, it is necessary to reflect upon how their personal attitudes and previous experiences influence the care of dying patients.